Cholesterol oxides inhibit cholesterol esterification by lecithin: cholesterol acyl transferase - Eder de Carvalho Pincinato; Patricia Moriel; Dulcinéia Saes Parra Abdalla (Universidade de São Paulo, 2009)
Cholesterol oxides are atherogenic and can affect the activity of diverse important enzymes for the lipidic metabolism. The effect of 7β-hydroxycholesterol, 7-ketocholesterol, 25-hydroxycholesterol, cholestan-3β,5α,6β-triol,5,6β-epoxycholesterol, 5,6α-epoxycholesterol and 7α-hydroxycholesterol on esterification of cholesterol by lecithin:cholesterol acyl transferase (LCAT, EC 2.3.1.43) and the transfer of esters of cholesterol oxides from high density lipoprotein (HDL) to low density lipoproteins (LDL) and very low density lipoproteins (VLDL) by cholesteryl ester transfer protein (CETP) was investigated. HDL enriched with increasing concentrations of cholesterol oxides was incubated with fresh plasma as source of LCAT. Cholesterol and cholesterol oxides esterification was followed by measuring the consumption of respective free sterol and oxysterols. Measurements of cholesterol and cholesterol oxides were done by gas-chromatography. 14C-cholesterol oxides were incorporated into HDL2 and HDL3 subfractions and then incubated with fresh plasma containing LCAT and CETP. The transfer of cholesterol oxide esters was followed by measuring the 14C-cholesterol oxide-derived esters transferred to LDL and VLDL. All the cholesterol oxides studied were esterified by LCAT after incorporation into HDL particles, competing with cholesterol by LCAT. Cholesterol esterification by LCAT was inversely related to the cholesterol oxide concentration. The esterification of 14C-cholesterol oxides was higher in HDL3 and the transfer of the derived esters was greater from HDL2 to LDL and VLDL. The results suggest that cholesterol esterification by LCAT is inhibited in cholesterol oxide-enriched HDL particles. Moreover, the cholesterol oxides-derived esters are efficiently transferred to LDL and VLDL. Therefore, we suggest that cholesterol oxides may exert part of their atherogenic effect by inhibiting cholesterol esterification on the HDL surface and thereby disturbing reverse cholesterol transport. Os óxidos de colesterol são aterogênicos e podem afetar a atividade de diversas enzimas importantes para o metabolismo lipídico. Este estudo investigou o efeito dos óxidos 7β-hidroxicolesterol, 7-cetocolesterol, 25-hidroxicolesterol, colestan-3β,5α,6β-triol, 5,6β-epoxicolesterol, 5,6α-epoxicolesterol e 7α-hidroxicolesterol na esterificação do colesterol por ação da lecitina colesterol aciltransferase (LCAT, EC 2.3.1.43) e a posterior transferência dos óxidos esterificados da lipoproteína de alta densidade (HDL) para as lipoproteínas de baixa densidade (LDL) e muito baixa densidade (VLDL) mediada pela proteína de transporte de éster de colesterol (CETP). Para atingir os objetivos, HDL enriquecida com concentrações crescentes de óxidos de colesterol foi incubada com plasma fresco pobre em lipoproteínas, como fonte de LCAT; posteriormente a esterificação do colesterol e dos óxidos de colesterol foi medida pelo consumo do colesterol livre e dos óxidos livres presentes na HDL. As determinações de colesterol e dos óxidos de colesterol foram realizadas por cromatografia gasosa. 14C-óxidos de colesterol foram incorporados nas subfrações HDL2 e HDL3 e posteriormente incubados com plasma fresco, contendo LCAT e CETP. A transferência dos ésteres de óxidos de colesterol foi medida e quantificada pela presença desses ésteres na LDL e VLDL. Todos os óxidos de colesterol estudados foram esterificados pela LCAT após incorporação nas partículas de HDL e competiram com a esterificação do colesterol nativo. A esterificação do colesterol pela LCAT foi inversamente relacionada à concentração de óxidos de colesterol. A esterificação dos óxidos de colesterol foi maior na HDL3 e a transferência desses ésteres foi maior a partir da HDL2 para a LDL e VLDL. Estes resultados indicam que a esterificação do colesterol pela LCAT é inibida nas partículas de HDL enriquecidas com óxidos de colesterol e que os ésteres de óxidos de colesterol são eficientemente transferidos para a LDL e VLDL. Portanto, sugere-se que os óxidos de colesterol exercem parte de seu efeito aterogênico pela inibição da esterificação do colesterol na superfície da HDL, causando um distúrbio no transporte reverso do colesterol, além de aumentar o potencial aterogênico da LDL e VLDL.